Schiffbruch mit Zuschauer: Paradigma einer Daseinsmetapher - Blumenberg, Hans (Frankfurt am Main Suhrkamp, 1979)
In his study Schiffbruch mit Zuschauer, the philosopher Hans Blumenberg compares shipwreck metaphors and their different uses with examples from the history of philosophy and literature from antiquity to the 20th century and uses them to demonstrate the change in philosophical points of view. In the appendix 'Ausblick auf eine Theorie der Unbegrifflichkeit', he presents his metaphorology, which states that there are insights that cannot be formulated in scientific conceptuality, but that can be illustrated with holistic imagery.
Includes bibliographical references.
Keywords: Philosophy